Peristaltic on-chip pump for tunable media circulation and whole blood perfusion in PDMS-free organ-on-chip and Organ-Disc systems. Issue 20 (31st August 2021) - Schneider, Stefan; Bubeck, Marvin; Rogal, Julia; Weener, Huub J.; Rojas, Cristhian; Weiss, Martin; Heymann, Michael; van der Meer, Andries D.; Loskill, Peter
Abstract : We present an Organ-Disc with integrated peristaltic pump for the closed-loop perfusion of microphysiological systems with tunable flow rates, enabling time-resolved monitoring of cell states and media properties, and the perfusion of whole blood. Abstract : Organ-on-chip (OoC) systems have become a promising tool for personalized medicine and drug development with advantages over conventional animal models and cell assays. However, the utility of OoCs in industrial settings is still limited, as external pumps and tubing for on-chip fluid transport are dependent on error-prone, manual handling. Here, we present an on-chip pump for OoC and Organ-Disc systems, to perfuse media without external pumps or tubing. Peristaltic pumping is implemented through periodic compression of a flexible pump layer. The disc-shaped, microfluidic module contains four independent systems, each lined with endothelial cells cultured under defined, peristaltic perfusion. Both cell viability and functionality were maintained over several days shown by supernatant analysis and immunostaining. Integrated, on-disc perfusion was further used for cytokine-induced cell activation with physiologic cell responses and for whole blood perfusion assays, both demonstrating the versatility of our system for OoC applications.